Anthropometric clinical indicators in the assessment of visceral obesity: an update - Roriz, Anna Karla Carneiro (2016)
Introduction: Visceral obesity is associated with an increased risk of metabolic disorders and occurrence of chronic diseases. The quantification of the visceral fat becomes necessary and advantageous in clinical practice, especially through accurate and precise methods in replacement of imaging methods as computed tomography (CT). Objective:To present the use of anthropometric indicators that have been linked to visceral fat. Methods: The selection of items was taken in from Scopus, Scielo, Lilacs, CAPES journals, PubMed/ MEDLINE and Google Scholar, in the period between 2007 and 2014. Anthropometric and clinical indicators as waist circumference (WC), waist- to- height ratio (WHtR), waist-to- thigh ratio (WTR), waist- to- hip ratio (WRH), sagittal abdominal diameter (SAD), abdominal diameter height index (SAD/ Height), abdominal diameter index (ADI), conicity index (CI), visceral adiposity index (VAI) and the lipid accumulation production (LAP) were investigated for their relationship with visceral fat measured by CT. Results: Most indicators have strong correlation (r>0.70) with visceral fat. It was observed that there are few recent studies evaluating this relationship, especially with the indices derived of the WC and the SAD, besides the LAP and the VAI. Most studies investigated the relationship between these indicators with the diseases that are consequent of the visceral obesity. Conclusion: The clinical anthropometric indicators are accurate in estimating visceral obesity, easy to use and has low cost enabling clinical nutritional assessment able to intervene earlier and more effectively in the prevention and/or treatment of this obesity._________________________________________________________________________________________ RESUMO: Introdução: A obesidade visceral está associada a um risco maior de distúrbios metabólicos e ocorrência de doenças crônicas. A quantificação da gordura visceral torna-se necessária e vantajosa na prática clínica, sobretudo por métodos acurados e precisos em substituição aos métodos por imagem, como a tomografia computadorizada (TC). Objetivo: Descrever a utilização de indicadores clí- nicos antropométricos que têm sido relacionados à gordura visceral. Métodos: A seleção dos artigos foi feita no Scopus, Scielo, Lilacs, periódicos Capes, Pubmed/Medline e Google Acadêmico, no período entre 2007 e 2014. Indicadores clínicos antropométricos como circunferência da cintura (CC), Razão cintura altura (RCA), Razão cintura coxa (RCCx), Razão Cintura Quadril (RCQ), Diâmetro abdominal sagital (DAS), Diâmetro abdominal altura (DAS/ALT), Índice Diâmetro abdominal (IDA), Índice conicidade (IC), Índice de adiposidade visceral (IAV) e o Produto de acumulação lipídica (PAL) foram investigados quanto sua relação com o tecido adiposo visceral medido pela TC. Resultados: A maioria dos indicadores tem forte correlação (r>0.70) com a gordura visceral. Observouse que há poucos estudos recentes que avaliaram essa relação, sobretudo com os índices derivados da CC e do DAS, além do PAL e o IAV. A maioria dos estudos investigou a relação entre esses indicadores com as doenças que são consequentes da obesidade visceral.